2020
DOI: 10.1186/s13287-020-01858-6
|View full text |Cite
|
Sign up to set email alerts
|

The co-culture of ASCs and EPCs promotes vascularized bone regeneration in critical-sized bone defects of cranial bone in rats

Abstract: Background: The repair of critical-sized bone defect represents a challenging problem in bone tissue engineering. To address the most important problem in bone defect repair, namely insufficient blood supply, this study aimed to find a method that can promote the formation of vascularized bone tissue. Method: The phenotypes of ASCs and EPCs were identified respectively, and ASCs/EPCs were co-cultured in vitro to detect the expression of osteogenic and angiogenic genes. Furthermore, the co-culture system combin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The AT-MSC/BM-EPC combination increases osteogenesis and angiogenesis-related gene expression in vitro. The results of animal experiments demonstrated that the AT-MSC/BM-EPC association accelerates critical-sized bone defect repair (He et al, 2020). Coculture of AT-MSC sheet-BM-EPCs generated more bone and cartilage.…”
Section: Sources Of Mscs In Coculturementioning
confidence: 98%
“…The AT-MSC/BM-EPC combination increases osteogenesis and angiogenesis-related gene expression in vitro. The results of animal experiments demonstrated that the AT-MSC/BM-EPC association accelerates critical-sized bone defect repair (He et al, 2020). Coculture of AT-MSC sheet-BM-EPCs generated more bone and cartilage.…”
Section: Sources Of Mscs In Coculturementioning
confidence: 98%
“…To this end, both cell types were co-cultured in vitro prior to co-implantation. Encouraging results, in terms of enhanced bone healing compared with implantation of osteogenic MSCs only, were obtained by combining co-cultured endothelial progenitor cells with bone marrow-or adipose-derived MSCs in HA-based scaffolds [87,88]. Interestingly, Xu et al [89] demonstrated that repair of critical size calvarial defects in rats can be promoted using osteogenic and endothelial cell sheets differentiated in vitro from bone marrow-derived MSCs, without the need for any scaffold providing structural support.…”
Section: Research On Cell-based Strategiesmentioning
confidence: 99%
“…Another method that has been evaluated for enhancing osteogenesis and neovascularization of augmented stem cells is co-culturing and co-transplantation of two different types of stem cells. Co-culturing and co-transplantation of ADSCs and endothelial progenitor cells (EPCs) has promoted bone regeneration and angiogenesis in a rat cranial defect 61 . In a study by Wu et al 62 , the addition of epithelial progenitor cells to BMMSCs has resulted in the upregulation of mRNA expressions of VEGF, osteonectin, osteopontin, and collagen type 1 and an increase in alkaline phosphatase activity and CD34.…”
Section: Future Prospectsmentioning
confidence: 99%